2015
DOI: 10.1637/11098-042015-reg
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Avian H7N9 Influenza A Viruses in the Yangtze Delta Region of China During Early H7N9 Outbreaks

Abstract: SUMMARY Since the first H7N9 human case in Shanghai, February 19, 2013, the emerging avian-origin H7N9 influenza A virus has become an epizootic virus in China, posing a potential pandemic threat to public health. From April 2 to April 28, 2013, 422 oral-pharyngeal and cloacal swabs were collected from birds and environmental surfaces at five live poultry markets (LPMs) and 13 backyard poultry farms (BPFs) across three cities, Wuxi, Suzhou, and Nanjing, in the Yangtze Delta Region. A total of 22 isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Despite significant efforts and resources dedicated to the control of these diseases, they remain a difficult challenge to face due to the increase in mobility between countries, and the difficulties of accessing treatment for some populations and for cases resistant to treatment [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant efforts and resources dedicated to the control of these diseases, they remain a difficult challenge to face due to the increase in mobility between countries, and the difficulties of accessing treatment for some populations and for cases resistant to treatment [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…While H7N9 is largely asymptomatic in poultry, it has resulted in more human deaths than H5 AIVs (Shi et al, 2017;Xiang et al, 2018) Li et al, 2016;Zeng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike for H5N1 and related viruses, the 2013 H7N9 AIVs is still restricted to China (FAO, 2019). The current level of vaccine coverage for H7N9 among chickens may be very high, and low H7N9 prevalence in pigeons, ducks and geese indicate that mass vaccination of the susceptible population may even eliminate or severely restrict the transmission of the virus (Jiang et al., 2019; Li et al., 2016; Zeng et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, 6,740 environmental samples collected and tested from LPMs in Zhejiang showed that 10.09% (680/6740) of the samples were H7N9-positive [16]. In April of 2013, 15 H7N9 viruses were isolated from 422 oral-pharyngeal and cloacal swabs collected from birds and environmental surfaces at five LPMs in Jiangsu [17]. In 2014, 6% (16/283; 4 chickens, 7 ducks, 1 goose, and 4 pigeons) of tracheal, cloacal, and fecal samples, collected from a variety of birds in poultry markets and farms in Jiangsu province, were positive for H7N9 viruses[18].…”
Section: Introductionmentioning
confidence: 99%